A Satellite Assessment of the Urban Heat Island in Morocco. Issue 1 (2nd January 2019) - Fathi, Najlaa; Bounoua, Lahouari; Messouli, Mohamed
Abstract: Urban ecosystems interact with surroundings via land cover changes and their subsequent impact on surface temperature. In emerging countries, large urban agglomerations often form around cities, and only a few studies have evaluated their impact. This study carries out the first ever large-scale assessment of urban heat island (UHI) and reflects on its mitigation in Morocco. The analysis reveals a well-defined UHI in urban areas built within vegetated lands and an urban heat sink (UHS) in urban areas built within arid regions. Both UHI and UHS amplitudes are higher during day than nighttime, emphasizing vegetation physiological activity. This study shows a monotonic increase in UHI amplitude with urban area size. However, unlike previous studies, this analysis shows that, as urban areas built in desert-like environments grow in size, the UHS gradually decreases to ultimately turn into an UHI. On average, cities built within vegetation are warmer than the rural fringe by 1.51 °C during daytime. This suggests that daytime urban heating may exacerbate the potential climate warming. These results also suggest that adapted trees constitute a natural cooling mechanism and should be part of urban heating mitigation in Morocco.